2022
DOI: 10.1177/09500170221128698
|View full text |Cite
|
Sign up to set email alerts
|

How Does Precarious Employment Affect Mental Health? A Scoping Review and Thematic Synthesis of Qualitative Evidence from Western Economies

Abstract: This article offers a scoping review and thematic synthesis of qualitative research on the relationship between precarious employment and mental health. Systematic searches of primary qualitative research in western economies, focused on insecure contracts and a broad conceptualisation of mental health, identified 32 studies. Thematic synthesis revealed four core experiences of precarious employment: financial instability, temporal uncertainty, marginal status and employment insecurity, each connected with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 102 publications
(242 reference statements)
0
7
0
Order By: Relevance
“…Based on theoretical pathways explaining how MEP affects workers’ subjective well-being, various experiences of MEP, such as low wages, employment insecurity, and temporal uncertainty, can lead to negative economic, relational, and behavioral responses. These negative responses include material hardship, presentism, and work-family conflict, which can ultimately result in the deterioration of mental health ( 49 ). Moreover, a recent mediation analysis conducted by Rivero et al ( 17 ) suggested that European workers with precarious jobs were more likely to be exposed to psychosocial risk factors, such as lack of social support and high job demands with little control, which contributed to the deterioration of having poor subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Based on theoretical pathways explaining how MEP affects workers’ subjective well-being, various experiences of MEP, such as low wages, employment insecurity, and temporal uncertainty, can lead to negative economic, relational, and behavioral responses. These negative responses include material hardship, presentism, and work-family conflict, which can ultimately result in the deterioration of mental health ( 49 ). Moreover, a recent mediation analysis conducted by Rivero et al ( 17 ) suggested that European workers with precarious jobs were more likely to be exposed to psychosocial risk factors, such as lack of social support and high job demands with little control, which contributed to the deterioration of having poor subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…These are all types of precarious employment which we know are associated with adverse mental health outcomes. 8 We understand that the authors wished to examine the relationship between future financial concerns at baseline (December 2020-March 2021) and depression symptoms at follow-up (June 2022-October 2022). At baseline, participants were asked 'How worried are you about your future financial situation?'…”
mentioning
confidence: 99%
“…These are all types of precarious employment which we know are associated with adverse mental health outcomes. 8 …”
mentioning
confidence: 99%
“… 5 Space has not permitted discussion of the role of “demand side” factors, in terms of stigma and employer reticence to recruit, support or retain employees who experience mental health difficulties [ 59 ], nor the quality of employment that may be available to individuals moving off benefits and the potentially damaging effects of precarious and insecure work on mental health [ 60 ]. However, we recognise the inextricable connection between our present discussion and the key issues of “good work” and mentally healthy workplaces.…”
mentioning
confidence: 99%